Oxygen‐Promoted CH Bond Activation at Palladium1. (9th May 2014) - Scheuermann, Margaret L.; Boyce, David W.; Grice, Kyle A.; Kaminsky, Werner; Stoll, Stefan; Tolman, William B.; Swang, Ole; Goldberg, Karen I.
Abstract [Pd(P(Ar)(tBu)2)2] (1, Ar=naphthyl) reacts with molecular oxygen to form PdII hydroxide dimers in which the naphthyl ring is cyclometalated and one equivalent of phosphine per palladium atom is released. This reaction involves the cleavage of both CH and OO bonds, two transformations central to catalytic aerobic oxidizations of hydrocarbons. Observations at low temperature suggest the initial formation of a superoxo complex, which then generates a peroxo complex prior to the CH activation step. A transition state for energetically viable CH activation across a Pdperoxo bond was located computationally.